Assembly and analysis of the complete mitochondrial and chloroplast genomes of Vigna reflexo-pilosa - Panthita Ruang-areerate; Suparat Pinsupa; Wasitthee Kongkachana; Thippawan Yoocha; Phakamas Phetchawang; Peeraphat Paenpong; Prakit Somta; Kularb Laosatit; Sithichoke Tangphatsornruang; Wirulda Pootakham (PLoS ONE, 2025)
Vigna reflexo-pilosa can be found in both wild and cultivated forms. It is the only tetraploid species in the genus Vigna in Fabaceae, occurring through hybridization between Vigna hirtella and Vigna trinervia, with the chromosome number of 2n = 4x = 44. V. reflexo-pilosa provides an invaluable gene pool for improving cultivated Vigna crop varieties. This study aimed to report the complete mitochondrial and chloroplast genomes of V. reflexo-pilosa. A total of 6,496,297 raw reads were generated from V. reflexo-pilosa using the long-read PacBio technology. The complete mitochondrial genome was assembled into a linear structure with a total length of 370,913 base pairs (bp) with 45.20% GC content. It contains 32 protein-coding genes, 18 transfer RNA genes, and 3 ribosomal RNA genes. A total of 520 RNA editing sites were detected in 30 protein-coding genes. The V. reflexo-pilosa mitochondrial genome shared large colinear blocks with Vigna radiata as compared to nine other mitochondrial genomes in Fabaceae. In addition, Vigna hirtella (male parent) and Vigna trinervia (female parent) were sequenced using the MGI sequencing technology. The complete chloroplast genome of V. reflexo-pilosa, V. hirtella, and V. trinervia was assembled into a circular structure with a total length of 150,967, 151,915 and 151,226 bp, respectively. All three chloroplast genomes consist of 128 genes. We found no evidence of shared genes between the mitochondrial and chloroplast genomes of V. reflexo-pilosa. Comparison of the three Vigna chloroplast genomes showed high levels of similarity between V. reflexo-pilosa and V. trinervia, revealing maternal inheritance of the chloroplast genomes. Based on both mitochondrial and chloroplast genes, phylogenetic trees showed that V. reflexo-pilosa is closely related to V. radiata. These genomes enhance our understanding of mitochondrial and chloroplast evolution of V. reflexo-pilosa and are valuable genetic resources in legumes.